Correcting Feedback on Essay Composition: EFL Students’ Preferences between Traditional and e-Feedback - Ariyanti Ariyanti; Dedi Rahman Nur (Yayasan Visi Intan Permata, 2017)
Writing is one of skills in English language proficiency which is considered as a complex and important element to passive communication. In addition, an ability of writing good composition has become one of requirements to successful life in many major aspects. Specifically to particular unit in learning writing in EFL classroom, feedback is the key for students to get their essay quality improved better. Therefore, this study is aimed to investigate feedback given by writing lecturer whether in traditional and e-feedback, as well as digging students’ preference towards those methods. Classroom observation and students’ open-ended questionnaires were used as major instruments, while semi-structured interview to writing lecturer was also used as supporting data. The result showed that most of the students prefer to be given the e-feedback to assess their essay instead of the traditional one. This study also reveals high expectation to the use of vary electronic media from the students, therefore future implication is clearly derived to the creativity of writing lecturer so that the students will be more motivated and surely improved in terms of structural and content aspects of writing.